A microfluidic device and instrument prototypes for the detection of Escherichia coli in water samples using a phage-based bioluminescence assay. Issue 11 (6th May 2022) - Alonzo, Luis F.; Hinkley, Troy C.; Miller, Andrew; Calderon, Ryan; Garing, Spencer; Williford, John; Clute-Reinig, Nick; Spencer, Ethan; Friend, Michael; Madan, Damian; Dinh, Van T. T.; Bell, David; et al.
Abstract : A phage-based microfluidic platform for highly sensitive and rapid detection of E. coli in low-resource settings. Abstract : Current quantification methods of Escherichia coli ( E. coli ) contamination in water samples involve long incubation, laboratory equipment and facilities, or complex processes that require specialized training for accurate operation and interpretation. To address these limitations, we have developed a microfluidic device and portable instrument prototypes capable of performing a rapid and highly sensitive bacteriophage-based assay to detect E. coli cells with detection limit comparable to traditional methods in a fraction of the time. The microfluidic device combines membrane filtration and selective enrichment using T7-NanoLuc-CBM, a genetically engineered bacteriophage, to identify 4.1 E. coli CFU in 100 mL of drinking water within 5.5 hours. The microfluidic device was designed and tested to process up to 100 mL of real-world drinking water samples with turbidities below 10 NTU. Prototypes of custom instrumentation, compatible with our valveless microfluidic device and capable of performing all of the assay's units of operation with minimal user intervention, demonstrated similar assay performance to that obtained on the benchtop assay. This research is the first step towards a faster, portable, and semi-automated, phage-based microfluidic platform for improved in-field water quality monitoring in low-resource settings.